The Importance of Cultural and Gastronomic Tourism in Local Economic Development: Zile Sample - Kocaman, Mehmet; Memis Kocaman, Emel (International Journal of Economics and Financial Issues, 2014)
More rational source distribution in Turkey recently has brought forward the principles of optimality in investment planning. Therefore, many rural areas have been negatively affected from this state. Accordingly, alternative tourism provides important opportunities for rural regions. People living in these regions have become to give importance to local tangible and intangible cultural assets, which are present around their environment and gastronomic products consisting of regional tastes. Zile District, Tokat Province in Turkey, could not receive sufficient share from state investments due to its location and therefore could not complete its economic development. This study expresses the elements regarding cultural and gastronomic tourism in Zile District and their contributions to regional economic development and indicates what should be done to get more effective benefits and to increase its positive contributions. Keywords: Local development; gastronomy; cultural tourism JEL Classifications: O12; R11